Jurnalisme Advokasi dalam Film Dokumenter Tenggelam dalam Diam - Denis Purna Eka Putra; Santi Indra Astuti (Bandung Conference Series: Journalism, 2022)
Abstract. Start from the interest of researchers in WatchDoc Docummentary Makers researchers view WatchDoc as an alternative media in voicing the rights of marginalized communities in addition they are also sensitive about environmental damage issues. One of his works Drowning In Silence is one of the works of WatchDoc Docummentary Makers that reveals the impact of abrasion that increasingly threatens residents around the coast. The research aims to find out the practice of advocacy journalism in the film Drowned In Silence by WatchDoc Docummentary Makers. This study uses qualitative research methods, researchers use qualitative data collection, namely in-depth interviews, used to find out the experiences or opinions of informants regarding issues that occur to prove the information or information that has been obtained. The focus of the film Drowning In Silence, The impact of the climate crisis is a disaster, especially for cities located around the island of Java, the cause can be concluded in programs that build roads, buildings and agricultural land. The issue raised in this documentary, this film tries to relate various climate crisis issues such as police narratives, or deforestation. The main resource persons in this research are the people who are in the most impacted areas caused by the flood disaster due to human activities. Documentary films are immersed in silence every minute presenting the facts of the impact of abrasion along with the views of the people who have suffered economic losses. It is hoped that the government will be able to provide solutions to coastal areas that have experienced and felt the impact of rising sea levels every year as well as disasters caused by heavy rains that cause flash floods that harm all aspects of the community elements who are usually the lower middle class. Journalism in this research is provocative in nature, there are several violations which have been determined regarding the policy of conserving Mangrove plants in order to restrain the rate of abrasion. Abstrak. Berawal dari ketertarikan peneliti terhadap WatchDoc Docummentary Makers peneliti memandang WatchDoc sebagai media alternatif dalam menyuarakan hak-hak masyarakat yang termarjinalkan selain itu mereka juga peka mengenai isu-isu kerusakan lingkungan. Salah satu karyanya Tenggelam Dalam Diam merupakan salah satu karya WatchDoc Docummentary Makers yang mengungkap dampak dari abrasi yang kian mengancam warga sekitar pesisir pantai. Penelitian ini bertujuan untuk mengetahui praktik jurnalisme advokasi dalam film Tenggelam Dalam Diam karya WatchDoc Docummentary Makers. Penelitian ini menggunakan metode penelitian kualitatif, peneliti menggunakan pengambilan data dengan cara kualitatif yaitu wawancara mendalam, digunakan untuk mengetahui pengalaman atau pendapat informan mengenai isuisu yang terjadi untuk membuktikan informasi atau keterangan yang telah diperoleh. Titik Berat dalam film Tenggelam Dalam Diam, Dampak dari krisis iklim menjadi bencana terutama bagi kota yang berada disekitaran pulau jawa, penyebab tersebut dapat disimpulkan pada program yang membangun jalanan, gedung sampai lahan pertanian. Isu yang diangkat dalam film dokumenter ini, Film ini mencoba mengaitkan berbagai permasalahan krisis iklim seperti narasi polisi, atau penggundulan hutan. Narasumber utama pada penlitian ini merupakan masyarakat yang berada didaerah paling berdampak yang dikarenakan oleh bencana banjir karena ulah manusia. Film dokumenter tenggelam dalam diam setiap menitnya menghadirkan fakta dari dampak abrasi disertai pandangan masyarkat yang mengalami kerugian ekonomi. Harapannya pemerintah mampu memberikan solusi kepada wilayah pesisir pantai yang sudah mengalami dan merasakan dampak dari kenaikan air laut setiap tahunnya serta bencana yang diakibatkan karena hujan deras yang menimbulkan banjir bandang yang merugikan seluruh aspek yang dimiliki oleh elemen-elemen masyarakat yang biasanya merupakan masyarakat menengah kebawah. Jurnalisme dalam penelitian ini bersifat provoaksi terdapat beberapa pelanggaran yang dimana sudah ditetapkan mengenai kebijakan melestarikan tanaman Mangrove guna menahan laju abrasi.